2015
DOI: 10.4236/msa.2015.611102
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Treatment and Cellulose Nanowhiskers Extracted from Maize Stalk Residues

Abstract: The aim of this study was to investigate the use of effect of pulveriser and extraction of cellulosenanowhiskers (CNWs) on Maize stalks. Maize stalk residues were first subjected to a cutting mill for size reduction purified using mechanical, chemical extraction and bleaching. After chemical extraction, high quality cellulose resulted and cellulose nanowhiskers (CNW) were then extracted using chemical acid hydrolysis. The chemical compositions and mechanical properties of the maize stalk residues were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…CNMs can be extracted from different natural sources (wood, non-woody and animal materials), by mechanical treatment and acid hydrolysis or combination of the two. They can broadly be grouped into five categories, viz., cellulose nanofibers (CNF), cellulose nanocrystals (CNCs), bacterial cellulose (BC), algal cellulose (AC), and tunicate cellulose depending on the source and extraction method, as discussed below [3,7,18,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…CNMs can be extracted from different natural sources (wood, non-woody and animal materials), by mechanical treatment and acid hydrolysis or combination of the two. They can broadly be grouped into five categories, viz., cellulose nanofibers (CNF), cellulose nanocrystals (CNCs), bacterial cellulose (BC), algal cellulose (AC), and tunicate cellulose depending on the source and extraction method, as discussed below [3,7,18,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, cellulose nanofibers are embedded in such matrix substances as hemicelluloses and lignin. Alkaline hydrolysis helped dissolve hemicelluloses (Motaung & Mtibe, ) and separate structural linkages between lignin and carbohydrates (Islam et al., ). Bleaching, which was applied after alkali hydrolysis, also helped eliminate phenolic groups in lignin, leading to the disruption of the lignin structure (Abraham et al., ; Motaung & Mtibe, ).…”
Section: Resultsmentioning
confidence: 99%
“…Alkaline hydrolysis helped dissolve hemicelluloses (Motaung & Mtibe, ) and separate structural linkages between lignin and carbohydrates (Islam et al., ). Bleaching, which was applied after alkali hydrolysis, also helped eliminate phenolic groups in lignin, leading to the disruption of the lignin structure (Abraham et al., ; Motaung & Mtibe, ). Previous works indeed reported similar decrease in the lignin content after alkaline treatment with NaOH and NaClO 2 (Rambabu, Panthapulakkal, Sain, & Dalai, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, this can be a good source of cellulosic bres. Furthermore, the few experimental-based research studies [3][4][5][6][7][8][9] on maize bres done till date have all shown that maize bre has proved to be interesting by reason of its appreciable mechanical and chemical properties. From literature, it has been noted that extraction of maize bres has been done by using either chemicals accompanied by boiling or milling equipment [3-5, 7, 9].…”
Section: Introductionmentioning
confidence: 99%